Effects of Sand Density and Reinforcement on the Behavior of Buried Tunnel - Majeed, Adel H.; Shannoon, Layth K. (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper aim to study the effects of earth reinforcement on the stresses generated within a semicircular cross-section tunnel lining buried in sandy soil due to surface loading. The effect of position and number of reinforcement layers was studied. Also, the relative density of soil was investigated. The depth of soil above the tunnel crown was fixed to be three times the tunnel radius. Two relative densities for soil were used, 55.3% and 73.3%. One layer of reinforcement that was used located at distance equal to the radius or two times the radius above tunnel crown. Also, two layers of reinforcement were located at distance equal to radius and two times radius above the tunnel crown. The results show that the use of earth reinforcement will reduce the stresses generated in the tunnel lining due to application of surface loading.